2014
DOI: 10.1093/ndt/gfu345
|View full text |Cite
|
Sign up to set email alerts
|

High-volume online haemodiafiltration improves erythropoiesis-stimulating agent (ESA) resistance in comparison with low-flux bicarbonate dialysis: results of the REDERT study

Abstract: In a uraemic patient population with low-grade inflammation treated with HV-OL-HDF, we observed a significant reduction of ERI values as well as HEP levels. The positive correlation between these two parameters supports a role for HEP in the development of ERI in the dialytic population. Moreover, the lower b2MG and the higher Kt/V achieved in HV-OL-HDF confirms the better depurative effect of this technique in comparison with BHD with respect to middle molecules and small-molecular-weight molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
68
3
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 42 publications
13
68
3
7
Order By: Relevance
“…The clearance is mild in low-flux HD, intermediate by high-flux HD, and elevated in OL-HDF. Recently, we demonstrated that the use of new HD techniques and more efficient membranes that allow higher convective volume, allow the removal of larger quantities of hepcidin with a significant reduction in pre- HD levels and a consensual improvement of ESAs resistance [33]. Also Stefansson et al [34], in a short-term study consisting of a small population of 20 patients, suggested that hepcidin levels were significantly reduced after 60 days of high volume OL-HDF with respect to low-flux HD.…”
Section: Current Strategies To Improve Esa Hyporesponsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The clearance is mild in low-flux HD, intermediate by high-flux HD, and elevated in OL-HDF. Recently, we demonstrated that the use of new HD techniques and more efficient membranes that allow higher convective volume, allow the removal of larger quantities of hepcidin with a significant reduction in pre- HD levels and a consensual improvement of ESAs resistance [33]. Also Stefansson et al [34], in a short-term study consisting of a small population of 20 patients, suggested that hepcidin levels were significantly reduced after 60 days of high volume OL-HDF with respect to low-flux HD.…”
Section: Current Strategies To Improve Esa Hyporesponsivenessmentioning
confidence: 99%
“…Small sample size randomized studies except Ward et al [39] showed an improvement of ERI or a reduction in ESAs consumption in post dilution OL-HDF (Lin et al [40], Vaslaki et al [41], Schiffl [42], Pedrini et al [43], and Panichi et al [33]). The study from Ward et al [39] failed to find a significant difference between online HDF and high-flux dialysis regarding the ERI but the sample size was very small, and the groups were not well balanced, particularly for the prevalence of polycystic kidney disease (8.3% in the HDF group vs. 23.8% in the HD group).…”
Section: Randomized and Observational Studiesmentioning
confidence: 99%
“…Many clinical effects for online HDF have been reported. These include the reduction of dialysis-related hypotension [6], improvement of anemia with sparing erythropoiesis-stimulating agent dosage [7,8,9], prevention of the deterioration of dialysis-related amyloidosis, improvement of the nutritional status by reducing inflammatory stress [10], cardiovascular protection by preserving vascular endothelial cell function [11,12], relief of both peripheral neuropathy and insomnia [13,14], preservation of residual renal function [15] and ultimately a survival benefit [3]. These effects are due to the better quality of dialysis fluid, the greater efficiency of removing uremic accumulates and the better hemodynamic stability during treatment resulting in prevention of dialysis-related hypotension.…”
Section: Expectation For Online Hdf From the Japanese Perspectivementioning
confidence: 99%
“…Increased phosphate removal, which was not found by the Italian group [19], is also expected to affect the serum calcification propensity and levels of calcified protein particles which are strongly related to the ectopic vascular calcification in ESRD patients. In addition, hepcidin removal is an important mechanism for the better management of anemia [9]. …”
Section: Clinical Effect Of Online Hdf: Further Expectationsmentioning
confidence: 99%
“…The benefit was attributed to the combined effects of the higher removal of middle-sized toxins (erythropoietic inhibitor substances) and reduced inflammation due to the use of higher-quality water and dialysis fluid [47,48]. However, this effect was not confirmed in a recent meta-analysis [49].…”
Section: Inflammation Oxidative Stress and Anemiamentioning
confidence: 99%